Novel approach and Cloud Point Extraction Method for Determination of Acetazolamide Drug (Indian Journal of Forensic Medicine & Toxicology, 2020)
Acetazolamide was hydrolyzed to primary aromatic amine by using (0.4) M NaOH under reflux. The product was evaluated by two a ways. The first way, Diazotization coupling reaction (approach) as simple, sensitive, rapid and selective Spectrophotometric method, using 8-hydroxyquinoline as Chromogenic reagent to give Azo dye (red) in basic medium. The second way involves applying Cloud point extraction, using Triton-x114 as surfactant. The Azo dye was diagnosed by FT-IR, 1HNMR and UV-Visible technique. The analytical data for Approach and Cloud point extraction method, involve concentration rang (5-150), (0.5-6) µg.mL-1, molar absorptivity (2.3×103), (1.3×104) L.mol-1.cm-1, Sandall’s sensitivity (0.096) µg.cm-2 (0.017) µg.cm-2 and detection limits (0.952) µg.mL-1 and (0.043) µg.mL-1 respectively. In addition the measurement enrichment factor (100) and preconcentration factor (6.30), The proposed methods don’t affect by the existence of excipients so the methods were applied successfully in determining Acetazolamide in pharmaceutical preparations
Keywords: Hydrolysis Acetazolamide, spectrophotometric determination, Cloud point extraction, Diazotization coupling reaction, 8-Hydroxyquinoline.